Understanding the Learner’s Course Completion in the New Normal: Graduation Cohort Analysis - San Pedro, Jay R; Baniago, Jocelyn; Sy, Cecilia (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The pandemic COVID-19 unveiled and magnified the various learning challenges experienced by learners which yield to learning gaps, losses, and higher dropout rates, especially in the tertiary level of education. With this, there is a need to investigate on how learners are able to complete their respective course programs in the new normal. This study attempted to understand the learner’s course completion through a graduation cohort analysis approach which is anchored on a quantitative-qualitative research design. Results uncovered that gender and residency of the learners are positively correlated to the length of their course completion. In addition, the course completion varies on the learners’ gender and residency. Furthermore, 79% of the learners were able to complete their course on-time with an average of 3.72 years and standard deviation of 1.09 years. Consequently, financial, mental-health, and lack of resources were the emerging reasons for the temporary discontinuation of their studies. Hence, these findings can be used as a basis for the Philippine Private Higher Education Institution to plan and implement an institutional learning recovery program.